Kewenangan polri dalam ruu serta pelanggaran hak asasi manusia - viona, amanah giovani visi yuti (Maliki Interdisciplinary Journal, 2026)
In the House of Representatives’ discussions since March 2024, the revision of Law Number 2 of 2002 concerning the Indonesian National Police (Polri) has raised concerns about the expansion of Polri’s repressive powers, which include cyber surveillance, wiretapping without court authorization, emergency detention for up to 72 hours, and the use of force without adequate oversight mechanisms. This study examines the potential threats to human rights, including privacy (Article 28G of the 1945 Constitution), fair legal process, and freedom of expression, with the risk of abuse of power and violations of the ICCPR. To gain an understanding of the legal and sociocultural context, the analysis was conducted through qualitative literature review. The results show that the new powers of the National Police could jeopardize privacy rights and civil liberties, including the possibility of discrimination against vulnerable groups. The journal also emphasizes the importance of having good oversight mechanisms and human rights protection measures to prevent abuse of authority. Ultimately, it is recommended that the law be comprehensively revised and that accountability and respect for human rights be prioritized.